Economists are the cheerleaders of finance - Mariana Mazzucato, The Value of Everything: Making and Taking in the Global Economy, London, Allen Lane, 2018, 384 pp., £14.99 (pbk), ISBN 978-0-241-34779-9 - David Hollanders (Finance and Society, 2018)
As the subtitle of her new book suggests, Mazzucato aims to distinguish value creators from value extractors. This distinction between making and taking, between earning and deserving, between rent-seeking and value-contributing, is posited as crucial, yet it can no longer be made from within the paradigm of neoclassical economics, which has defined the distinction out of existence. Mazzucato shows this was not always so: classical economists did make the distinction, as did preceding economic schools such as the Physiocrats. This, however, is not a purely intellectual exercise; Mazzucato seeks to influence public debate, stating that “only by debunking ideas about value … can a long-lasting solution be found” (213), the problem being that what the financial sector, pharmaceutical companies, and national account statisticians call ‘value creation’ is in fact typically the opposite.